Faktor Determinan Turnover Intention Perawat di Rumah Sakit Islam Surabaya - Qanitah, Qanitah; Muhadi, Muhadi; Indahyati, Emilya (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2022)
The turnover rate in RSI Surabaya for the last 5 years, namely 2017-2021, has increased by an average of 18.14%. High turnover rates can have a negative and positive impact on hospitals. The occurrence of turnover begins with the desire to leave, the desire to leave work can be caused by several factors including individual factors and job satisfaction factors. This study aims to determine individual determinants and job satisfaction related to nursing turnover intention at RSI Surabaya. The method used in this study is a quantitative analytical approach with a cross-sectional design, and sampling technique with simple random sampling and the sample in this study was 126 nurses. Data analysis used univariate and bivariate tests (correlation tests of Kendall's tau-b). The Results nurses who work at RSI Surabaya feel quite satisfied with job satisfaction (the job itself, salary, promotion opportunities, supervision, and co-workers). The incidence of nurse turnover intention at RSI Surabaya is included in the moderate category. The determinant factor of individuals related to the turnover intention of nurses at RSI Surabaya is the marital status with a significant value of 0.021, while the determinant factor of job satisfaction related to turnover intention in RSI is satisfaction with salary, with a significant value obtained of 0.027. The more unmarried nurses, the higher the turnover intention, and the lower the level of satisfaction with the salary, the higher the turnover intention.